Photoprotective efficiency of PLGA-curcumin nanoparticles versus curcumin through the involvement of ERK/AKT pathway under ambient UV-R exposure in HaCaT cell line. (April 2016) - Chopra, Deepti; Ray, Lipika; Dwivedi, Ashish; Tiwari, Shashi Kant; Singh, Jyoti; Singh, Krishna P.; Kushwaha, Hari Narayan; Jahan, Sadaf; Pandey, Ankita; Gupta, Shailendra K.; Chaturvedi, Rajnish Kumar; Pant, Aditya Bhushan; et al.
Abstract: Curcumin (Cur) has been demonstrated to have wide pharmacological window including anti-oxidant and anti-inflammatory properties. However, phototoxicity under sunlight exposure and poor biological availability limits its applicability. We have synthesized biodegradable and non-toxic polymer-poly (lactic-co-glycolic) acid (PLGA) encapsulated formulation of curcumin (PLGA-Cur-NPs) of 150 nm size range. Photochemically free curcumin generates ROS, lipid peroxidation and induces significant UVA and UVB mediated impaired mitochondrial functions leading to apoptosis/necrosis and cell injury in two different origin cell lines viz., mouse fibroblasts-NIH-3T3 and human keratinocytes-HaCaT as compared to PLGA-Cur-NPs. Molecular docking studies suggested that intact curcumin from nanoparticles, bind with BAX in BIM SAHB site and attenuate it to undergo apoptosis while upregulating anti-apoptotic genes like BCL2. Real time studies and western blot analysis with specific phosphorylation inhibitor of ERK1 and AKT1/2/3 confirm the involvement of ERK/AKT signaling molecules to trigger the survival cascade in case of PLGA-Cur-NPs. Our finding demonstrates that low level sustained release of curcumin from PLGA-Cur-NPs could be a promising way to protect the adverse biological interactions of photo-degradation products of curcumin upon the exposure of UVA and UVB. Hence, the applicability of PLGA-Cur-NPs could be suggested as prolonged radical scavenging ingredient in curcumin containing products. Graphical abstract: Graphical representation showing photoprotective mechanism of PLGA-Cur-NPs under ambient environmental ultra-violet radiation exposure.